An assisted solid phase additive manufacturing method and apparatus
By processing microporous structures on the substrate surface and combining dynamic temperature control and multi-focus laser welding, the problems of high deposition pressure, low interfacial bonding strength, and inaccurate temperature control in solid-phase additive manufacturing have been solved, enabling efficient and reliable manufacturing of thin-walled components of dissimilar metals that meet the performance and airtightness requirements of high-end applications.
Patent Information
- Application Number
- CN202611129981.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-28
- Publication Date
- 2026-11-03
AI Technical Summary
Existing solid-state additive manufacturing technology suffers from problems such as excessively high deposition pressure, insufficient interfacial bonding strength, poor temperature control accuracy, and low reliability of final sealing connection in the joining of dissimilar metals. In particular, it is difficult to meet the requirements of high-end applications in the manufacturing of thin-walled components of high-melting-point metals.
Ultrafast lasers are used to process microporous structures on the substrate surface. Combined with dynamic feedback algorithms to adjust the laser output power and temperature, the deposition process is controlled in real time. Plastic rheological filling is performed through a solid-phase deposition head at a temperature below the material's melting point, and high-strength and hermetic connections are achieved using multi-focus laser welding technology.
It achieves high interfacial shear strength and efficient deposition of dissimilar metal thin-walled components, with temperature control accuracy reaching ±10℃, high deposition layer density, meeting the performance requirements of high-end applications, and an airtight welding leakage rate of less than 1×10-8 Pa·m3/s.
Smart Images

Figure CN123024976A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an additive manufacturing method and apparatus, specifically to an assisted solid-phase additive manufacturing method and apparatus, belonging to the field of metal additive manufacturing technology. Background Technology
[0002] In aerospace, new energy vehicles, and high-end equipment industries, the demand for dissimilar metal thin-walled components with aluminum / steel and aluminum / titanium composite structures is growing. These components typically require a balance of lightweight, high load-bearing capacity, and reliable sealing. However, the low miscibility and significant differences in thermophysical properties between dissimilar metal materials make it easy for nanoscale brittle intermetallic compounds (IMCs) to form at the interface when using traditional melting additive manufacturing or joining techniques, leading to a sharp deterioration in the interfacial mechanical properties.
[0003] Solid-state additive manufacturing technologies such as friction stir additive manufacturing and triboelectric deposition additive manufacturing are considered important technical routes for joining dissimilar metals because they avoid complete melting of materials and can effectively suppress the formation of brittle intermetallic compounds. However, existing solid-state additive manufacturing technologies still have technical bottlenecks. For high-melting-point metals such as titanium alloys and high-strength steel, due to their extremely high rheological stress at solid-state temperatures, conventional processes require the application of axial deposition pressures exceeding 30 MPa. This not only leads to bulky equipment structures and a sharp increase in energy consumption, but also easily causes warping deformation of thin-walled components, and severe wear of the stirring tools results in a short service life.
[0004] Furthermore, in solid-state additive manufacturing, reducing the rheological resistance of high-melting-point metals and optimizing interfacial bonding through temperature control remains a technical challenge. Due to the lack of temperature control methods that are matched in real time with dynamic deposition conditions, external heat input is difficult to adapt to fluctuations in travel speed and changes in material heat dissipation conditions. Temperature fluctuations often exceed ±50℃, resulting in unstable softening or strengthening effects and a narrow process window.
[0005] Meanwhile, existing technologies generally lack pre-depositional microstructure design of the deposition interface, resulting in interface tensile strength typically below 150 MPa, which cannot meet the stringent requirements of high-end applications.
[0006] Furthermore, regarding the final sealing connection of components, such as the welding of dissimilar steel / aluminum components between the battery pack water-cooling plate and the steel frame, it is necessary to simultaneously meet the requirements of high strength and ultra-high airtightness, with a leakage rate of <1×10⁻⁶. -8 Pa·m 3 / s, conventional single-focus laser welding is prone to defects such as spatter and porosity, making it difficult to achieve the above-mentioned performance indicators. Summary of the Invention
[0007] Based on the above background, the purpose of this invention is to provide an auxiliary solid-phase additive manufacturing method and apparatus to solve the problems of excessively high deposition pressure, insufficient interfacial bonding strength, poor temperature control accuracy, and low reliability of final sealing connection in the existing dissimilar metal solid-phase additive manufacturing technology.
[0008] To achieve the above-mentioned objectives, the present invention provides the following technical solution: An assisted solid-state additive manufacturing method, the method comprising the following steps: Ultrafast lasers are used to selectively scan and etch the substrate surface to be deposited, creating a regularly arrayed microporous structure or trench structure. The temperature information of the substrate is collected in real time by a thermometer, and the output power of the auxiliary laser is dynamically adjusted by a dynamic feedback algorithm to scan and heat the area of the substrate to be deposited, so that the temperature of the area to be deposited is within the set target temperature range. Solid metal deposition material is conveyed, and the solid phase deposition head is controlled to apply axial pressure to the solid metal deposition material, causing the solid metal deposition material to undergo plastic rheology at a temperature below its melting point and fill into the microporous structure or trench structure processed on the substrate surface, thereby forming a solid phase deposition layer on the substrate.
[0009] Preferably, the ultrafast laser has a pulse width of less than 500 fs, a power of 10~50 W, a scanning speed of 100~500 mm / s, and a scanning line spacing of 20~50 μm; the micropore structure or the trench structure has an average aperture of 20~80 μm, a depth of 10~50 μm, and a surface coverage of 30%~60%.
[0010] Preferably, the target temperature range for scanning heating of the deposition area of the substrate is included, specifically a switchable preheating softening mode and a self-quenching mode. The preheating and softening mode is as follows: the target temperature range is set to a first temperature range that is lower than the melting point of the substrate and is in a plasticized state, and the area to be deposited is softened and preheated before the solid phase deposition head applies axial pressure to the solid metal deposition material. The self-quenching mode is as follows: the target temperature range is set to the second temperature range of austenitization or solid solution of the matrix material; before the solid phase deposition head applies axial pressure to the solid metal deposition material, the area to be deposited is scanned and heated; when the solid phase deposition head applies axial pressure to the solid metal deposition material, heat exchange cooling is performed through the contact between the unheated solid metal deposition material and the heated area to be deposited.
[0011] Preferably, when the substrate or the solid metal deposition material contains titanium alloy, the preheating softening mode is executed, and the first temperature range is 400~600℃; when the substrate contains aluminum alloy, the self-quenching mode is executed, and the second temperature range is 350~450℃.
[0012] Preferably, a dynamic feedback algorithm is used to dynamically adjust the output power of the auxiliary laser, specifically including: The output power of the auxiliary laser is adjusted according to the real-time feeding speed of the solid metal deposition material using the following formula: ; In the formula, To enhance the output power of the auxiliary laser, As the reference laser power, For the real-time feeding speed of solid metal deposition materials, As the baseline feeding speed, The absorption coefficient of the substrate for the laser emitted by the auxiliary laser is given.
[0013] Preferably, during the initial stage of scanning and heating of the auxiliary laser, the auxiliary laser is controlled to output in a DC constant power mode; after entering the steady-state deposition stage, the polarity duty cycle in the output power modulation of the auxiliary laser is gradually increased.
[0014] Preferably, the method further includes: The surface of the solid-phase deposited layer is milled to control the layer thickness error to no more than 0.05 mm and the surface roughness to be [specific parameters]. Within the range of ≤2.1μm.
[0015] An auxiliary solid-state additive manufacturing apparatus employing the auxiliary solid-state additive manufacturing method described above, the apparatus comprising: A solid-phase deposition head is used to apply axial pressure to the solid metal deposition material; A feeding mechanism is used to deliver solid metal deposition material to the solid phase deposition head; An ultrafast laser surface roughening unit is located on the front side of the solid-phase deposition head along the additive manufacturing direction, and is used to perform micro-nano etching on the surface of the substrate to be deposited. An auxiliary laser heating unit includes an auxiliary laser, a scanning galvanometer, and a thermometer. The optical axis of the auxiliary laser is inclined relative to the axis of the solid deposition head, and is used to heat the deposition area of the substrate. The control unit is electrically connected to the feeding mechanism, the ultrafast laser surface roughening unit, the auxiliary laser heating unit, and the solid-phase deposition head, respectively, and is used to control the operation of the feeding mechanism, the ultrafast laser surface roughening unit, the auxiliary laser heating unit, and the solid-phase deposition head based on real-time acquired data on feeding speed, substrate temperature, axial pressure, and torque.
[0016] Preferably, the auxiliary laser is a continuous fiber laser with a rated output power of 3~12 kW; the thermometer is a fiber optic thermometer with a temperature measurement range of 650~1600℃, a sampling frequency of ≥6kHz, and a response time of ≤167μs; the control unit is equipped with a temperature process controller with a control frequency of ≥12.5kHz, and the temperature process controller is configured to run a power control program based on a flight heating algorithm and variable polarity duty cycle adjustment.
[0017] Preferably, the device further includes: The mechanical subtractive finishing unit is located on the rear side of the solid-phase deposition head along the additive manufacturing direction and is used to perform cutting processing on the surface after solid-phase deposition.
[0018] Compared with the prior art, the present invention has the following advantages: This invention discloses an auxiliary solid-state additive manufacturing method and apparatus that achieves a breakthrough in the manufacturing technology of thin-walled components made of dissimilar metals through the synergistic effect of ultrafast laser micro / nano surface texturing, dual-mode laser temperature control, and solid-state deposition. Femtosecond laser roughening forms a microporous array without a heat-affected zone on the substrate surface, providing physical anchoring points for ductile metals. Temperature control, through a fly-by-flight heating algorithm and variable polarity duty cycle modulation, keeps temperature fluctuations within ±10℃, ensuring the stability of preheating softening or in-situ quenching effects. Solid-state deposition achieves plastic rheological filling at temperatures below the material's melting point, avoiding the formation of brittle intermetallic compounds. Simultaneously, the preheating effect reduces the deposition pressure to 15 MPa or below, effectively solving the deformation problem of high-melting-point thin-walled metal parts. This synergy enables the aluminum / steel interface shear strength to exceed 260 MPa, increases the hardness of the aluminum alloy substrate by 20%~30%, achieves deposition efficiency more than twice that of traditional processes, and maintains a component layer thickness error of no more than 0.05 mm, with overall performance surpassing the manufacturing level of existing technologies. Attached Figure Description
[0019] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the provided drawings without creative effort.
[0020] Figure 1This is a schematic diagram of the structure of an auxiliary solid-phase additive manufacturing apparatus according to the present invention; Figure 2 This is a schematic diagram of the auxiliary laser in this invention; Figure 3 This is a schematic flowchart of an assisted solid-phase additive manufacturing method according to the present invention; Figure 4 This is a temperature-time curve diagram under the self-quenching mode in this invention; Figure 5 This is a temperature-time curve diagram under the preheating and softening mode in this invention; Figure 6 This is a schematic diagram of the spiral / mesh feature path of PFO scanning within 1 mm in the preheating and softening mode of this invention; Figure 7 This is an analysis diagram of the grain structure after laser softening in the preheating softening mode of this invention; Figure 8 This is a schematic diagram of the multi-focus laser welding principle in this invention; In the diagram: 1. Solid phase deposition head; 2. Feeding mechanism; 3. Ultrafast laser surface roughening unit; 4. Auxiliary laser heating unit; 5. Control unit; 6. Mechanical subtractive finishing unit; 7. Subtractive tool magazine; 8. Laser online detection unit; 9. AC axis turntable; 401. Rear objective lens; 402. Line laser emitter; 403. Deflector mirror thermal fuse; 404. Heat shield. Detailed Implementation
[0021] The technical solution of the present invention will be further described in detail below through specific embodiments and in conjunction with the accompanying drawings. It should be understood that the implementation of the present invention is not limited to the following embodiments, and any modifications and / or alterations made to the present invention will fall within the protection scope of the present invention.
[0022] Unless otherwise specified, the methods described in the following embodiments are conventional methods in the art. Unless otherwise specified, the components or devices in the following embodiments are general standard parts or components known to those skilled in the art, and their structures and principles can be obtained by those skilled in the art through technical manuals or conventional experimental methods.
[0023] An embodiment of the present invention discloses an auxiliary solid-state additive manufacturing apparatus, such as... Figure 1 As shown, the device includes a solid-phase deposition head 1, a feeding mechanism 2, an ultrafast laser surface roughening unit 3, an auxiliary laser heating unit 4, and a control unit 5.
[0024] The solid-state deposition head 1 is configured to apply axial pressure to the solid metal deposition material. It is equipped with pressure sensors, torque sensors, and speed sensors to monitor the mechanical state during the deposition process in real time. The feeding mechanism 2 is configured to feed the solid metal deposition material to the solid-state deposition head 1, and the feeding speed can be adjusted within the range of 5~30 m / min according to process requirements. The ultrafast laser surface roughening unit 3 is located at the front of the solid-state deposition head 1 along the additive manufacturing direction. It is configured to perform micro-nano etching on the surface of the substrate to be deposited. It uses an ultrafast laser with a pulse width of less than 500 fs and forms a regularly arrayed micropore structure or trench structure on the substrate surface through a scanning optical system. The auxiliary laser heating unit 4 includes an auxiliary laser, a scanning galvanometer, and a thermometer. The auxiliary laser is configured to heat the area of the substrate to be deposited, and its optical axis is tilted relative to the axis of the solid-state deposition head 1 at an angle of 15°~25°. This tilted arrangement helps to concentrate laser energy onto the area to be deposited in front of the deposition head, while avoiding optical path interference and reducing contamination of optical components by splashes. The control unit 5 is electrically connected to the feeding mechanism 2, the ultrafast laser surface roughening unit 3, the auxiliary laser heating unit 4, and the solid phase deposition head 1, respectively, and is configured to control the operation of the feeding mechanism 2, the ultrafast laser surface roughening unit 3, the auxiliary laser heating unit 4, and the solid phase deposition head 1 based on the real-time collected data of feeding speed, substrate temperature, axial pressure, and torque.
[0025] In addition, the device includes a mechanical subtractive finishing unit 6, a subtractive tool magazine 7, a laser online inspection unit 8, and an AC-axis rotary table 9. The mechanical subtractive finishing unit 6 is located behind the solid-state deposition head 1 along the additive manufacturing direction and is configured to perform cutting machining on the surface after solid-state deposition. The laser online inspection unit 8 is used to monitor the morphology and temperature field distribution of the deposited layer in real time, providing feedback information to the control unit 5. The subtractive tool magazine 7 stores milling tools of various specifications to meet the needs of tool changing for finishing. The AC-axis rotary table 9 enables multi-angle posture adjustment of the workpiece, adapting to the additive manufacturing needs of complex curved surfaces.
[0026] The detailed structural features of the auxiliary laser heating unit 4 are as follows: Figure 2As shown. The auxiliary laser includes a rear objective lens 401, a line laser emitter 402, a deflector thermal fuse 403, and a heat shield 404 to protect the optical components. The rear objective lens 401 is used to focus and shape the laser beam, the line laser emitter 402 is used to project structured light to assist in topography detection, the deflector thermal fuse 403 automatically cuts off the optical path under overheating conditions to protect downstream components, and the heat shield 404 effectively isolates the high-temperature deposition area from thermal radiation to the precision optical components. Specifically, in this embodiment, the auxiliary laser is a continuous fiber laser with a rated output power of 3~12 kW, using the TruDisk series laser with a wavelength of 1030 nm. The thermometer is a fiber optic thermometer with a temperature measurement range of 650~1600℃, a sampling frequency ≥6kHz, and a response time ≤167μs. The scanning galvanometer uses a PFO 20-2 type galvanometer scanning system, which has high-precision two-dimensional deflection capability and can achieve spiral / grid feature path scanning within a range of 1 mm.
[0027] The temperature control logic of control unit 5 is as follows: a fiber optic thermometer acquires the substrate surface temperature signal in real time and transmits it to the temperature process controller. The temperature process controller has a built-in power control program based on a flight heating algorithm and variable polarity duty cycle adjustment. Based on the deviation between the set target temperature and the actual measured temperature, it calculates and outputs control commands to the scanning galvanometer and laser. The scanning galvanometer adjusts the spatial scanning trajectory of the laser beam, and the laser adjusts its output power to ensure that the laser energy distribution and intensity irradiating the substrate surface matches the process requirements in real time. This control logic enables high-speed communication between modules through a data interaction interface. The control frequency of the temperature process controller is ≥12.5kHz, which meets the bandwidth requirements for real-time control.
[0028] like Figure 3 As shown in the figure, an embodiment of the present invention also discloses an assisted solid-phase additive manufacturing method, the specific implementation process of which is as follows.
[0029] First, an ultrafast laser micro / nano texturing step is performed. An ultrafast laser beam with a pulse width of less than 500 fs is used to selectively scan and etch the substrate surface to be deposited, fabricating a regularly arrayed micropore or trench structure. The laser power is set to 10–50 W, the scanning speed to 100–500 mm / s, and the scan line spacing to 20–50 μm. The average aperture of the fabricated micropore or trench structure is 20–80 μm, the depth to 10–50 μm, and the surface coverage to 30%–60%. Due to the extremely short pulse duration of the ultrafast laser, the material absorbs the laser energy but does not have time to diffuse through thermal conduction; it directly transforms from a solid state to a plasma state and is ejected for removal. Therefore, there is no heat-affected zone in the etched area, avoiding the thermal damage and recast layer problems caused by traditional long-pulse laser processing. This micro-nano texturing step forms a large number of three-dimensional anchor points on the substrate surface. When the subsequent solid metal deposition material undergoes plastic flow under axial pressure, the metal is forced to fill the micropores or trenches. After cooling and shrinkage, its interlocking strength is much higher than the frictional bonding of planar contact.
[0030] The temperature control step is then executed. The temperature information of the substrate is acquired in real time using a fiber optic thermometer with a measurement range of 650~1600℃, a sampling frequency ≥6 kHz, and a response time ≤167μs. The thermometer transmits the temperature signal to the temperature process controller in control unit 5. The temperature process controller runs a dynamic feedback algorithm, namely a power control program based on a fly-through heating algorithm and variable polarity duty cycle adjustment, to dynamically adjust the output power of the auxiliary laser, thereby scanning and heating the area of the substrate to be deposited, so that the temperature of the area to be deposited is within the set target temperature range.
[0031] The temperature control includes two switchable control modes. The first is a preheating and softening mode, which sets the target temperature range to a first temperature range below the melting point of the substrate and in a plasticized state. For example, when the substrate or solid metal deposition material contains titanium alloy, this first temperature range is 400~600℃. Before the solid phase deposition head 1 applies axial pressure to the solid metal deposition material, the area to be deposited is softened and preheated, reducing the surface flow stress of the substrate by more than 50%, thereby allowing effective plastic deformation under significantly reduced axial pressure. The second is a self-quenching mode, which sets the target temperature range to a second temperature range where the substrate material is austenitized or solution-treated. For example, when the substrate contains aluminum alloy, this second temperature range is 350~450℃. Before applying axial pressure to the solid deposition head 1, the area to be deposited is scanned and heated to bring the substrate to the solid solution temperature. When the axial pressure is applied to the deposition head, the solid metal deposition material in the unheated state is cooled by heat exchange through contact with the heated area to be deposited. This cooling rate is much higher than conventional furnace cooling or air cooling, which can achieve in-situ self-quenching phase transformation strengthening and increase the hardness of the substrate by 20% to 30%.
[0032] like Figure 4 and Figure 5 As shown in the figure, the process thermophysical property characteristic diagram compares the temperature-time curves of the self-quenching mode and the preheating softening mode. In the self-quenching mode, the matrix temperature is rapidly raised to the austenitizing or solution temperature range, and then rapidly cooled through contact with the cold solid metal deposition material, resulting in a temperature curve that shows a rapid rise followed by a sharp drop. In the preheating mode, the matrix temperature is maintained in the plasticizing state range, and the temperature curve is relatively stable. The figure also shows the curve of the material hardness decreasing with temperature after heating, indicating that the material hardness decreases significantly and the flow stress decreases in the preheating softening mode, while the hardness can recover through rapid cooling in the self-quenching mode. Figure 6 As shown, the schematic diagram of the spiral / mesh feature path of PFO scanning within 1 mm illustrates the uniform coverage of laser energy in the area to be deposited, and this scanning path ensures the spatial uniformity of heat input. Figure 7 The analysis of grain structure after laser softening in preheating softening mode is presented.
[0033] The specific process of dynamically adjusting the output power of the auxiliary laser using the dynamic feedback algorithm is as follows.
[0034] The output power of the auxiliary laser is adjusted according to the real-time feeding speed of the solid metal deposition material using the following formula: ; In the formula, To enhance the output power of the auxiliary laser, As the reference laser power, For the real-time feeding speed of solid metal deposition materials, As the baseline feeding speed, The absorption coefficient of the substrate for the laser emitted by the auxiliary laser is denoted as .
[0035] By directly linking the feeding speed to the laser power, the laser power is linearly adjusted when the feeding speed fluctuates due to equipment vibration, material inhomogeneity, or changes in path curvature, ensuring constant heat input per unit length and thus controlling temperature fluctuations within ±10℃, solving the problem of temperature overshoot caused by speed fluctuations in traditional open-loop control.
[0036] In the initial stage of scanning heating with the auxiliary laser, the auxiliary laser is controlled to output in DC constant power mode. In this mode, the laser rapidly heats the substrate with a constant power, shortening the temperature settling time and reaching the target temperature range as quickly as possible. Once the steady-state deposition stage begins, the variable polarity duty cycle in the output power modulation of the auxiliary laser is gradually increased. This variable polarity modulation, by periodically changing the effective duty cycle of the laser output, introduces periodic power troughs while maintaining the average power to meet temperature requirements. This helps reduce the heat accumulation effect in the steady-state stage, prevents surface overheating and abnormal grain growth, and optimizes the microstructure of the heat-affected zone.
[0037] Next, a solid-state deposition step is performed. Solid metal deposition material is fed in, and axial pressure, not exceeding 15 MPa, is applied to the material by the solid-state deposition head 1. The solid metal deposition material undergoes plastic flow at temperatures below its melting point. This plastic deformation mechanism differs from melting and solidification; the material maintains its solid lattice structure while achieving macroscopic flow through dislocation slip and grain boundary diffusion. The plastically deformed solid metal deposition material fills the microporous or trench structures processed on the substrate surface, forming a solid-state deposition layer on the substrate. Due to the three-dimensional constraint of the micropores or trenches, the filler metal and the substrate form a firmly bonded fit, significantly improving the interfacial bonding strength. The deposition layer density is ≥99.9%, and the layer thickness error is ≤0.05 mm.
[0038] Finally, an in-situ subtractive finishing process is performed. The surface of the solid-phase deposited layer is milled to control the layer thickness error to no more than 0.05 mm and the surface roughness Ra ≤ 2.1 μm. The mechanical subtractive finishing unit 6 is located on the rear side of the solid-phase deposition head 1 along the additive manufacturing direction, forming a continuous operation with the deposition process. It promptly removes surface flash and irregular protrusions generated during the deposition process, achieving high-precision forming.
[0039] Finally, for components requiring a final sealed connection, multi-focus laser welding technology can be used. For example... Figure 8 As shown, a single laser beam is split into four parts by a beam splitter, forming a central spot and an annular spot on the workpiece surface, constituting a core-ring energy distribution pattern. The central spot provides sufficient energy to penetrate the material and form a keyhole, while the outer annular spot provides stable support to the keyhole wall, suppressing violent oscillations and collapse of the keyhole. This significantly reduces spatter and porosity, achieving the technical effect of stabilizing the keyhole and suppressing spatter, thus meeting the requirements for ultra-high airtightness welding.
[0040] Application Example 1 This application example demonstrates the process of manufacturing a steel-aluminum composite-aluminum three-layer water-cooled plate using the method and apparatus of this invention. The water-cooled plate must meet the requirements of high strength and high airtightness welding with the steel battery box.
[0041] Base material preparation: A steel-aluminum composite plate is used, with an outer layer of 304 stainless steel (1.0 mm thick) and an inner layer of 6061 aluminum alloy (0.8 mm thick). A 0.05 mm nickel foil barrier layer is placed between the two layers. The plate is formed by hot rolling. The tensile strength is ≥310 MPa, and the interfacial shear strength is ≥100 MPa. 3003 aluminum alloy rods with a diameter of 20 mm are used as the deposition material to additively form the inner flow channel plate on the aluminum layer of the composite plate.
[0042] Femtosecond laser surface roughening: An ultrafast laser with a pulse width of 350 fs, a power of 25 W, and a wavelength of 1030 nm was used. Scanning parameters were set as follows: scanning speed 300 mm / s, line spacing 30 μm, and a spiral filling path. The treatment area was the entire surface of the composite aluminum layer, measuring 500 mm × 200 mm. Roughening results: A micropore array with an average pore size of 55 μm, a depth of 25 μm, and a surface coverage of 48% was formed, with no heat-affected zone. The contact angle decreased from 78° before treatment to 32°, indicating a significant improvement in surface wettability, which is beneficial for subsequent filling and spreading of ductile metal.
[0043] Laser preheating (self-quenching mode) and temperature control: The goal was to rapidly heat the surface of the aluminum layer in the composite plate to the quenching temperature, and then achieve self-quenching by cooling the deposited aluminum layer. A TruDisk 4001 continuous fiber laser with a power of 3 kW and a spot diameter of 6 mm (defocus + 5 mm) was used as the auxiliary laser. A fiber optic pyrometer was used as the temperature sensor, with a measurement range of 650~1600℃ and a response time of 167 μs. The control process was executed by a temperature process controller, with a target temperature set at 400℃ (±10℃). The initial feeding speed was 10 mm / s, the measured temperature was 390~408℃, the power was dynamically adjusted between 2.8~3.2 kW, and the heating time was approximately 1.2 s. Results: The surface hardness of the aluminum layer in the composite plate increased from 65 HV to 82 HV, an increase of 26%, with significant grain refinement.
[0044] Solid-phase deposition: deposition head rotation speed 1200 rpm, axial pressure 12 MPa, feed rate 12 mm / s, target deposition layer thickness 0.8 mm. During deposition, a fiber optic pyrometer is used for real-time monitoring to maintain the deposition interface temperature at 320~350℃ (below the melting point of aluminum).
[0045] Results: The deposited layer density was 99.94%, the layer thickness error was ≤0.04 mm, and the surface roughness Ra=2.1μm. The average interfacial shear strength test result was 168 MPa (5 samples, highest 175 MPa). The fracture surface showed that the aluminum filling in the micropores was pulled apart, exhibiting ductile fracture characteristics.
[0046] Final multifocal laser welding: The outer 304 stainless steel layer of the water-cooled plate was butt-welded to the steel frame of the battery pack (MS1200, 2.0mm thick). The laser source was a TruDisk 8001 with a power of 8 kW and a wavelength of 1030nm. The optical system used a BEO D70 with a multifocal beam splitter and a focal length of 200mm. The welding speed was 8m / min, the shielding gas was argon with a flow rate of 20L / min, and the defocusing amount was 0mm.
[0047] Results: The weld surface was smooth, without spatter, and X-ray inspection revealed no porosity. The helium leak test showed a leakage rate of 3.2 × 10⁻⁶. - 9 Pa·m 3 / s, better than the target value of 1×10 -8 Pa·m 3 / s. The tensile strength of the welded joint is 312 MPa (base material fracture). It passed the vibration test (10~500 Hz, 2g) and the water tightness test (0.3 MPa, 5min without leakage).
[0048] Application Example 2 This application example demonstrates the application of the present invention in the manufacture of thin-walled structures of high-melting-point metal (TC4 titanium alloy).
[0049] Substrate and deposition material: The substrate is a 2.0 mm thick TC4 titanium alloy plate in the annealed state. The deposition material is a 16 mm diameter TC4 titanium alloy bar.
[0050] Femtosecond laser roughening: Parameters are the same as in Application Example 1, forming micropores on the substrate surface. Testing showed that the interfacial shear strength increased by approximately 18% after roughening.
[0051] Laser preheating (preheating and softening mode): Target temperature 500℃, reducing the rheological stress of the titanium alloy to less than 50% of that before preheating. Laser power 4kW, spot diameter 8mm, temperature closed-loop control, fluctuation ±8℃. Preheating is continuous, feeding speed 20mm / s.
[0052] Solid phase deposition: deposition head rotation speed 800 rpm, axial pressure 14 MPa, feed rate 20 mm / s (high-speed mode). 8 layers were deposited, with a total thickness of 6 mm and a width of 15 mm.
[0053] Results: The sedimentary layer had a density of 99.92%, a tensile strength of 1050 MPa (comparable to the parent material), and an elongation of 7.5%. The deposition efficiency was approximately 2500 cm³. 3 / h, compared to conventional friction stir additive manufacturing (approximately 800 cm²). 3 / h) increases by 3 times.
[0054] Comparative Example 1 This comparative example is a contrast application without femtosecond coarsening, used to verify the necessity of the coarsening step.
[0055] The experimental conditions were exactly the same as in Application Example 1, but the femtosecond laser roughening step was omitted.
[0056] Results: The interfacial shear strength decreased to 102 MPa, a 39% decrease compared to Example 1, and the fracture surface showed a smooth interfacial peel morphology. This comparative result indicates that femtosecond roughening is crucial for enhancing interfacial bonding strength, and omitting this step will lead to a significant deterioration in interfacial performance.
[0057] Comparative Example 2 This comparative example demonstrates the application of conventional laser welding to verify the technical advantages of multi-focal welding.
[0058] Experimental conditions: The same water-cooled plate and steel frame as in Application Example 1 were used, but conventional single-focus laser welding was employed with a power of 6kW and a speed of 6m / min.
[0059] Results: Significant spatter was observed in the weld, and X-ray inspection revealed a dense distribution of pores with diameters ranging from 0.2 to 0.5 mm. The helium leak detection rate was 8.5 × 10⁻⁶. -7 Pa·m 3 / s, does not satisfy ≤1×10 -8 The design requirements were not met, and the airtightness test failed. This comparative result demonstrates that multi-focus laser welding, through its core-ring energy distribution stabilization of the keyhole morphology and suppression of spatter and porosity, plays an irreplaceable role in achieving ultra-high airtightness welding.
[0060] Based on the test results of the above application examples, the technical effects of the present invention can be presented in Table 1.
[0061] Table 1 Comparison of Test Results The data comparison above shows that, compared with Application Example 3, under the premise that other process parameters are basically the same, the interfacial shear strength is significantly increased from 102 MPa to 168 MPa, an increase of 65%, simply due to the introduction of the femtosecond laser roughening step. This significant difference stems from the micropore array constructed on the substrate surface by femtosecond laser roughening. When the solid metal deposited material undergoes plastic flow under axial pressure and fills the micropores, the interlocking structure formed by cooling can effectively resist shear loads, changing the interface failure mode from smooth interface peeling to ductile fracture of the metal filled in the micropores. The geometric parameters of the micropores (pore diameter 20~80 μm, depth 10~50 μm, surface coverage 30%~60%) are optimized to ensure sufficient interlocking volume to provide mechanical anchoring force, while avoiding stress concentration caused by excessively large pore diameter and weakening of substrate strength caused by excessively high surface coverage.
[0062] The comparison between Application Example 1 and Application Example 4 reveals the role of multi-focus laser welding in achieving ultra-high airtightness. Application Example 4 uses conventional single-focus laser welding, and its leakage rate is more than two orders of magnitude higher than that of Application Example 1, which cannot meet the stringent airtightness requirements of applications such as battery packs.
[0063] Application Example 2 demonstrates the role of the preheating softening mode in the manufacturing of high-melting-point metals. TC4 titanium alloy exhibits extremely high rheological stress at room temperature, requiring conventional solid-state additive manufacturing to apply axial pressures exceeding 30 MPa, leading to severe deformation of thin-walled parts and rapid tool wear. By preheating the substrate to 400–600 °C, the rheological stress of the titanium alloy is reduced by more than 50%, allowing the deposition pressure to be controlled at a lower level of 14 MPa, while simultaneously increasing the deposition rate to 20 mm / s and achieving an efficiency of 2500 cm⁻¹. 3 / h. The synergistic effect of preheating softening and femtosecond roughening is reflected in the fact that preheating reduces the deformation resistance of the material, making it easier for ductile metals to fill micropores, while the presence of micropores enhances the interfacial bonding of the deposited layer, compensating for the strength loss that may be caused by preheating.
[0064] The fly-through heating algorithm in the dynamic feedback algorithm directly correlates laser power with real-time feeding speed. When the feeding speed fluctuates due to equipment vibration, material inhomogeneity, or changes in path curvature, the laser power can respond instantly, maintaining a constant heat input per unit length. Compared with traditional fixed-power open-loop control, this algorithm reduces temperature fluctuations from above ±50℃ to within ±10℃, providing a foundation for preheating softening or quenching control. Variable polarity duty cycle modulation further optimizes the spatiotemporal distribution of heat input. The high-power DC output in the initial stage quickly establishes the temperature field, shortening process preparation time. In the steady-state stage, variable polarity modulation, through periodic power modulation, introduces a thermal cycling effect while maintaining the average temperature, promoting grain refinement and suppressing the formation of overheated structures.
[0065] In summary, this invention achieves a performance breakthrough in the field of dissimilar metal thin-walled component manufacturing through the systematic integration of ultrafast laser micro / nano surface texturing, dual-mode laser temperature control, solid-state deposition, and multi-focus laser welding, forming a tight synergistic mechanism.
[0066] This article uses specific examples to illustrate the principles and implementation methods of the present invention. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of the present invention. It should be noted that those skilled in the art can make several improvements and modifications to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the protection scope of the claims of the present invention.
Claims
1. An assisted solid-state additive manufacturing method, characterized in that: The method includes the following steps: Ultrafast lasers are used to selectively scan and etch the substrate surface to be deposited, creating a regularly arrayed microporous structure or trench structure. The temperature information of the substrate is collected in real time by a thermometer, and the output power of the auxiliary laser is dynamically adjusted by a dynamic feedback algorithm to scan and heat the area of the substrate to be deposited, so that the temperature of the area to be deposited is within the set target temperature range. Solid metal deposition material is conveyed, and the solid phase deposition head is controlled to apply axial pressure to the solid metal deposition material, causing the solid metal deposition material to undergo plastic rheology at a temperature below its melting point and fill into the microporous structure or trench structure processed on the substrate surface, thereby forming a solid phase deposition layer on the substrate.
2. The assisted solid-state additive manufacturing method according to claim 1, characterized in that: The ultrafast laser has a pulse width of less than 500 fs, a power of 10~50 W, a scanning speed of 100~500 mm / s, and a scanning line spacing of 20~50 μm; the micropore structure or the trench structure has an average aperture of 20~80 μm, a depth of 10~50 μm, and a surface coverage of 30%~60%.
3. The assisted solid-state additive manufacturing method according to claim 1, characterized in that: The target temperature range for scanning heating of the deposition area of the substrate specifically includes a switchable preheating softening mode and a self-quenching mode. The preheating and softening mode is as follows: the target temperature range is set to a first temperature range that is lower than the melting point of the substrate and is in a plasticized state, and the area to be deposited is softened and preheated before the solid phase deposition head applies axial pressure to the solid metal deposition material. The self-quenching mode is as follows: the target temperature range is set to the second temperature range of austenitization or solid solution of the matrix material; before the solid phase deposition head applies axial pressure to the solid metal deposition material, the area to be deposited is scanned and heated; when the solid phase deposition head applies axial pressure to the solid metal deposition material, heat exchange cooling is performed through the contact between the unheated solid metal deposition material and the heated area to be deposited.
4. The assisted solid-state additive manufacturing method according to claim 3, characterized in that: When the substrate or the solid metal deposition material contains titanium alloy, the preheating softening mode is executed, and the first temperature range is 400~600℃; when the substrate contains aluminum alloy, the self-quenching mode is executed, and the second temperature range is 350~450℃.
5. The assisted solid-state additive manufacturing method according to claim 1, characterized in that: The output power of the auxiliary laser is dynamically adjusted using a dynamic feedback algorithm, specifically including: The output power of the auxiliary laser is adjusted according to the real-time feeding speed of the solid metal deposition material using the following formula: ; In the formula, To enhance the output power of the auxiliary laser, As the reference laser power, For the real-time feeding speed of solid metal deposition materials, As the baseline feeding speed, The absorption coefficient of the substrate for the laser emitted by the auxiliary laser is given.
6. The assisted solid-state additive manufacturing method according to claim 1, characterized in that: During the initial stage of scanning and heating of the auxiliary laser, the auxiliary laser is controlled to output in DC constant power mode; after entering the steady-state deposition stage, the polarity duty cycle in the output power modulation of the auxiliary laser is gradually increased.
7. The assisted solid-state additive manufacturing method according to claim 1, characterized in that: The method also includes: The surface of the solid-phase deposited layer is milled to control the layer thickness error to no more than 0.05 mm and the surface roughness to be [specific parameters]. Within the range of ≤2.1μm.
8. An auxiliary solid-state additive manufacturing apparatus employing the auxiliary solid-state additive manufacturing method as described in any one of claims 1-7, characterized in that: The device includes: A solid-phase deposition head is used to apply axial pressure to the solid metal deposition material; A feeding mechanism is used to deliver solid metal deposition material to the solid phase deposition head; An ultrafast laser surface roughening unit is located on the front side of the solid-phase deposition head along the additive manufacturing direction, and is used to perform micro-nano etching on the surface of the substrate to be deposited. An auxiliary laser heating unit includes an auxiliary laser, a scanning galvanometer, and a thermometer. The optical axis of the auxiliary laser is inclined relative to the axis of the solid deposition head, and is used to heat the deposition area of the substrate. The control unit is electrically connected to the feeding mechanism, the ultrafast laser surface roughening unit, the auxiliary laser heating unit, and the solid-phase deposition head, respectively, and is used to control the operation of the feeding mechanism, the ultrafast laser surface roughening unit, the auxiliary laser heating unit, and the solid-phase deposition head based on real-time acquired data on feeding speed, substrate temperature, axial pressure, and torque.
9. An auxiliary solid-state additive manufacturing apparatus according to claim 8, characterized in that: The auxiliary laser is a continuous fiber laser with a rated output power of 3~12 kW; the thermometer is a fiber optic thermometer with a temperature measurement range of 650~1600℃, a sampling frequency of ≥6kHz, and a response time of ≤167μs; the control unit is equipped with a temperature process controller with a control frequency of ≥12.5kHz, and the temperature process controller is configured to run a power control program based on a flight heating algorithm and variable polarity duty cycle adjustment.
10. An auxiliary solid-state additive manufacturing apparatus according to claim 8, characterized in that: The device also includes: The mechanical subtractive finishing unit is located on the rear side of the solid-phase deposition head along the additive manufacturing direction and is used to perform cutting processing on the surface after solid-phase deposition.
